Morphological variations of explosive residue particles and implications for understanding detonation mechanisms - Abdul-Karim, Nadia; Blackman, Christopher S.; Gill, Philip P.; Morgan, Ruth M.; Matjacic, Lidija; Webb, Roger; Ng, Wing H. (American Chemical Society, 2016)
The possibility of recovering undetonated explosive residues following detonation events is well-known; however, the morphology and chemical identity of these condensed phase postblast particles remains undetermined. An understanding of the postblast explosive particle morphology would provide vital information during forensic examinations, allowing rapid initial indication of the explosive material to be microscopically determined prior to any chemical analyses and thereby saving time and resources at the crucial stage of an investigation. In this study, condensed phase particles collected from around the detonations of aluminized ammonium nitrate and RDX-based explosive charges were collected in a novel manner utilizing SEM stubs. By incorporating the use of a focused ion beam during analysis, for the first time it is possible to determine that such particles have characteristic shapes, sizes, and internal structures depending on the explosive and the distance from the detonation at which the particles are recovered. Spheroidal particles (10–210 μm) with microsurface features recovered following inorganic charge detonations were dissimilar to the irregularly shaped particles (5–100 μm) recovered following organic charge firings. Confirmatory analysis to conclude that the particles were indeed explosive included HPLC-MS, Raman spectroscopy, and mega-electron volt–secondary ionization mass spectrometry. These results may impact not only forensic investigations but also the theoretical constructs that govern detonation theory by indicating the potential mechanisms by which these particles survive and how they vary between the different explosive types.